Konsentrasi Sorbitol dan Volume Larutan Terbaik pada Cetakan Film Edibel dari Pati Sagu - Siti Fatima; Abdullah Abdullah; Masriani Masriani; Hasriani Hasriani (Institut Pertanian Bogor, 2023)
This study aims to determine the effect of sorbitol concentration and solution volume on the mold on the physical properties of the edible film from sago strach. This research was conducted at the Laboratory of Agricultural Sciences STIP Mujahidin Tolitoli, Tuweley Village, Baolan District, Tolitoli Regency, Central Sulawesi Tengah from October to December 2020. This study used a factorial completely randomized design (FCRD). The first factor (a) is the concentration of sorbitol, namely a1 (5 mL/100 mL solution), a2 (6 mL/100 mL solution), and a3 (7 mL/100 mL solution) while the second factor (m) is the volume of the solution in the mold, namely m1 (5 mL), m2 (10 mL), and m3 (15 mL). The data were analyzed using variance followed by the 1% Duncant Multiple Range Test (DMRT). The results showed that the addition of sorbitol concentration had an effect on the color, thickness, and solubility in water, while the addition of solution volume in the mold affected the color, thickness and water vapor transmission. The best treatment due to the addition of sorbitol concentration to edible film is 5% sorbitol concentration treatment, namely the color has a high brightness level, 0.19 mm thickness, and 41.5% solubility. While the best treatment due to the addition of the volume of the solution on the edible film is the treatment of the 5 ml solution volume, namely the color has a high level of brightness, a thickness of 0.14 mm and a water vapor transmission of 1.11g/m2.hour. Keywords: edible film, sago starch, sorbitol